Evaluating the relationship between family role performance levels and health perceptions of individuals: a cross-sectional study in primary care - Fatma Karasu; Filiz Polat (Universidade Estadual de Maringá, 2022)
The aim of this study is to examine the relationship between family role performance levels and health perceptions of individuals. This cross-sectional study was conducted with 438 participants who applied to four Family Health Centers between 18 July 2020 and 18 November 2020. The data were collected using Personal Information Form, Family Role Performance Scale, and Perception of Health Scale. ANOVA, independent samples t test and regression test were used for statistics calculations. Ethics Committee approval and institutional permissions were obtained to conduct the study. Scale mean scores of the participants were 30.92 ± 6.41 for Family Role Performance Scale and 48.35 ± 7.73 for Perception of Health Scale. As a result of simple linear regression analysis, a significant correlation was found between Family Role Performance and Perception of Health Scale. According to regression analysis, it was determined that family role performance affected health perception at the rate of 15.1%. In this study, it was determined that as family role performance increased, the level of health perception also increased, and there was a correlation between family role performance and health perception. Family role performances and health perception for all participants were at a moderate level